The Rough Guide to South Africa. - Pinchuck, Tony, ....-; McCrea, Barbara, ....- (London : Rough Guides, 2010)
The Rough Guide to South Africa is the most comprehensive and informative guide available to this spectacular country. You'll find detailed information on everything from hiking in the mysterious Drakensberg to sampling wine in the many Western Cape's estates. Updated specifically for travelers visiting South Africa for the football World Cup in 2010, Lesotho and Swaziland have been excluded from the book allowing for more in-depth information on how to tackle the World Cup in this edition. Whether you want to wander the pastel-colored streets of the Bo-Kaap, explore the Garden Route's dramatic Storms River Mouth, or get spine-tinglingly close to lions and other big game in Kruger National Park; this guide will lead you to the best attractions in South Africa. The Rough Guide to South Africa features up-to-date reviews of all the hottest new places to stay from hotels to community minded accommodations and tour companies. Find the best restaurants, shops, bars and clubs in South Africa across every price range giving you balanced reviews and honest, first-hand opinions. Explore all corners of the country with authoritative background on everything from local cuisine to desert wildlife, relying on comprehensive maps and practical language tips.
Keywords: Zuid-Afrika -- Reisgidsen